Foreign Direct Investment in Less Developed Countries: Impact on Home Countries - Franko, Lawrence G. (Journal of International Business Studies, 1978)
In the past, governments in advanced countries have generally considered that direct foreign investment (DFI) in less developed countries (LDCs) had beneficial, or at least neutral, effects on their own developed national economies. This view has recently come under attack from advanced-country unions concerned with “job loss,” businessmen concerned with competition from LDCs, and government officials concerned with relative declines in technological strengths.